A MODEL FOR DETERMINING THE SAFETY LEVEL OF OCCUPATIONAL WORK USING ACCIDENTS AND INJURIES MEASUREMENT PARAMETERS: A REVIEW - T. A. YUSUF; O. M. SANUSI; H. O. ADEYEMI (Journal of Engineering Studies and Research)
Frequency Rate (FRR), Fatality Rate (FAR) and Severity Rate (SR) are common parameters used in communicating the research output of occupational accidental injuries. These parameters have been used to provide a model for classifying an occupational work activity into five level/degrees of safety ranging between Very Safe and Highly Unsafe. With a work activity defined as x: x ≤ 0.01, x ≤ 0.003 or x ≤ 0.03 indicates Very Safe Level while x > 0.04, x > 0.015 or x>0.11 indicates Highly Unsafe Level according to FRR, SR and FAR respectively. A case study is provided from an existing work to experiment the application of the model.